Starbucks - 2007 - Karthik, D.; Dixit, Mukund R. ([London] : SAGE, 2016)
This case describes the financial and non-financial performance of Starbucks, a large organisation provided as on 2007. Howard Schultz, the promoter and chairman of the corporation is disturbed by the decline in the performance of Starbucks, especially the dilution of customer experience. He is required to analyse what happened and adopt a course of action to strengthen Starbucks' performance vis a vis competitive attacks. The participants are required to analyse the situation, generate options for Starbucks and make recommendations for the future, including whether Jim Donald, the current incumbent, needs to be retained as the CEO of Starbucks.
Originally Published in: Karthik, D., & Dixit, M. R. (2015). Starbucks - 2007. BP0389. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Starbucks Coffee Company; Competition -- Case studies; Corporate governance -- Case studies; Performance -- Case studies